2016
DOI: 10.1080/01913123.2016.1187689
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive human neuroblastomas show a massive increase in the numbers of autophagic vacuoles and damaged mitochondria

Abstract: Autophagy is activated in cancer cells in response to multiple stresses and has been demonstrated to promote tumor cell survival and drug resistance in neuroblastoma (NB). This study was conducted to analyze the ultrastructural features of peripheral neuroblastic tumors (pNTs) and identify the relation of the types of NTs, the proliferation rate, and MYCN gene amplification with a number of autophagic vacuoles. Our results indicate that aggressive human NBs show a massive increase in the number of autophagic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Autophagy serves an important role in the proliferation of colorectal cancer cells ( 3 ), and a number of studies have suggested that autophagy prevents metabolites from damaging cells and genomes ( 4 , 5 ). Conversely, other studies have suggested that autophagy contributes to the supply of nutrients and reused metabolites to tumor cells, therefore promoting their survival and proliferation ( 6 , 7 ). Although autophagy has been demonstrated to affect the proliferation of tumor cells, the regulatory mechanism underlying autophagy in colon cancer cells has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy serves an important role in the proliferation of colorectal cancer cells ( 3 ), and a number of studies have suggested that autophagy prevents metabolites from damaging cells and genomes ( 4 , 5 ). Conversely, other studies have suggested that autophagy contributes to the supply of nutrients and reused metabolites to tumor cells, therefore promoting their survival and proliferation ( 6 , 7 ). Although autophagy has been demonstrated to affect the proliferation of tumor cells, the regulatory mechanism underlying autophagy in colon cancer cells has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the number of NSGs in tumours with an unfavorable prognosis, could be explained either by an increase in the rate of their biogenesis or a disorder that effects the regulatory mechanisms of autophagy in these cells (11). Disruption in autophagy, the catabolic process in which a cell digests and eliminates its own macromolecules and organelles, could link the relatively larger number of NSGs to a poor prognosis (12).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that oxidative stress is enhanced in NB, and indeed our previous microarray data showed an increase of SOD mRNA expression, as well as altered expression of genes involved in glutathione metabolism [ 24 ]. Moreover, an ultra-structural study on NB primary tumors recently showed consistent auto-phagic vacuoles and abnormality of mitochondria structure in all undifferentiated NB cells [ 31 ]. Therefore, it cannot be excluded that the impaired erythrocyte maturation observed in patients with NB was a peculiar effect consequent to the disruption of mitochondria in this particular lineage, and impairment of mitochondria structure and/or function may be a more general feature of NB tumors.…”
Section: Discussionmentioning
confidence: 99%